Preparation method of injectable hydrogel based on schizophyllan, its product and application
Through the preparation method of injectable hydrogel based on cleavage polysaccharides, the problem that hyaluronic acid is difficult to maintain structural stability in the body for a long time is solved, and a physical hydrogel that exists stably in the body is obtained for a long time is obtained, which reduces the injection frequency and improves the effect and safety of cosmetic plastic surgery.
Patent Information
- Application Number
- CN202411052988.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-01
AI Technical Summary
It is difficult for existing hyaluronic acid to maintain structural stability in the body for a long time, and multiple injections are required to maintain the effect, which causes inconvenience to patients.
A physical hydrogel with a stable network structure is constructed by using the preparation method of injectable hydrogel based on cracked polysaccharides.
The obtained cracked polysaccharide physical gel exists stably in the body for a long time and has excellent water retention and water absorption, reducing the injection frequency and improving the effect and safety of cosmetic plastic surgery.
Smart Images

Figure CN118978716B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and relates to a preparation method of an injectable hydrogel based on schizophyllan, a product thereof and an application thereof. Background Art
[0002] In today's society, people's pursuit of beautiful appearance is constantly rising, so much so that cosmetic plastic surgery has been widely used around the world to reduce signs of aging and restore youth. However, traditional plastic surgery often requires cutting and suturing tissues, which has high risks and complexity. In order to meet patients' needs for safety, convenience and natural beauty, injectable gels have gradually attracted attention as a new technology. Injectable gels refer to materials that can be injected into subcutaneous tissue in a liquid or semi-fluid state and can form a gel-like substance in the target area after injection to fill tissue loss, eliminate wrinkles and improve facial contours. Injectable gels have been widely welcomed due to their advantages such as low risk, few complications, short recovery time and easy operation.
[0003] Hyaluronic acid (HA) has become a common hydrogel material in the field of cosmetic surgery because of its good biocompatibility and water absorption and moisturizing properties. However, it is difficult for hyaluronic acid to maintain its structural stability in the body for a long time, and multiple injections are usually required to maintain the effect, which brings inconvenience to patients. In view of this, we selected schizophyllan (SPG), which has a chemical structure similar to hyaluronic acid, as a new type of filling material for injectable beauty. Compared with hyaluronic acid, schizophyllan shows better effects in moisturizing, repairing and beautifying, and due to the lack of corresponding decomposing enzymes in the human body, schizophyllan can exist stably in the body for a long time. Therefore, providing an environmentally friendly method for preparing a hydrogel of schizophyllan is an urgent problem to be solved. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a method for preparing an injectable hydrogel based on Schizophyllan, and a product and application thereof.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing an injectable hydrogel based on Schizophyllan, the preparation method comprising:
[0007] (1) concentrating the aqueous solution containing Schizophyllan to obtain Schizophyllan pregel;
[0008] (2) soaking the schizophyllan pregel in an organic solvent to obtain an organogel;
[0009] (3) subjecting the organogel to a wet annealing treatment;
[0010] (4) Soaking the gel obtained in step (3) in deionized water and freeze-drying to obtain the gel.
[0011] Schizophyllan is a naturally occurring high molecular weight polysaccharide, and its unique rigid triple helical structure and abundant hydroxyl groups give it excellent water retention and water absorption. At the same time, the hydroxyl groups on Schizophyllan can also react with other molecules to prepare chemically cross-linked hydrogels. The preparation method of the present invention relies on the molecular structure of Schizophyllan. Under suitable conditions, Schizophyllan can unwind into a single-chain structure and re-aggregate into a triple helical structure under specific conditions. Therefore, by regulating the topological structure of the aggregates in the polymer network, a physical hydrogel with a stable network structure can be constructed. The method of the present invention has a simple process, the raw materials are cheap and easy to obtain, and there is no biological toxicity, which is conducive to process mass production.
[0012] The present invention provides a preparation method of wet annealing, which controls the hydrogen bond interaction between schizophyllan molecular chains and their crystallization characteristics, thereby regulating the pore size, water absorption, drug release, mechanical properties and injectability of hydrogel materials. The obtained schizophyllan physical gel is an environmentally friendly material.
[0013] Preferably, the concentration temperature in step (1) is 60-90° C. and the time is 2-5 h.
[0014] The temperature can be selected as 60℃, 62℃, 65℃, 68℃, 70℃, 72℃, 75℃, 78℃, 80℃, 82℃, 85℃, 88℃, 90℃, etc., and the time can be selected as 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h, 5h, etc. Other specific point values within the above numerical range can be selected, so they will not be elaborated here.
[0015] Preferably, the mass percentage of Schizophyllan in the Schizophyllan pregel in step (1) is 5-60%, for example 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. Other specific point values within the above numerical range can be selected and will not be described here one by one.
[0016] Preferably, the organic solvent in step (2) comprises any one of dimethylacetamide, dimethyl sulfoxide, formamide, acetonitrile, or a combination of at least two thereof.
[0017] Preferably, the immersion time in the organic solvent is 6-72h, for example 6h, 8h, 10h, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h, 40h, 42h, 45h, 48h, 50h, 52h, 55h, 58h, 60h, 62h, 65h, 68h, 70h, 72h, etc. Other specific point values within the above numerical range can be selected, which will not be described one by one here.
[0018] Preferably, the organic solvent is replaced every 2-3 hours, for example, 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc. Other specific point values within the above numerical range can be selected, which will not be described here one by one.
[0019] Preferably, the wet annealing temperature is 100-150° C. and the time is 3-72 hours.
[0020] The temperature can be selected as 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc., and the time can be selected as 3h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, 72h, etc. Other specific point values within the above numerical range can be selected, so they will not be described one by one here.
[0021] Preferably, the soaking time in step (4) is 7-10 days, for example 7 days, 8 days, 9 days, 10 days, etc. Other specific points within the above numerical range can be selected and will not be described in detail here.
[0022] Preferably, in step (4), the deionized water is replaced every 20-28 hours, for example, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, etc. Other specific point values within the above numerical range can be selected and will not be described here one by one.
[0023] When the gel was immersed for the above-mentioned number of days and the deionized water was replaced at a specific time, the organic solvent in the gel was completely exchanged.
[0024] In a second aspect, the present invention provides a hydrogel prepared according to the preparation method described in the first aspect.
[0025] The preparation method of the hydrogel obtained by the present invention uses only one organic solvent, and deionized water is used for immersion exchange in the subsequent preparation method. The final product does not contain organic solvent, is environmentally friendly, and has a wider range of applications.
[0026] The preparation method of the present invention finally exchanges all the organic solvents, and the obtained hydrogel does not contain organic components and is safer.
[0027] In a third aspect, the present invention provides a use of the hydrogel according to the second aspect in cosmetics.
[0028] Schizophyllan polysaccharide shows excellent effects in moisturizing, repairing and beautifying. The resulting hydrogel does not contain organic solvents, making it safer to use in cosmetics.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention provides a preparation method of wet annealing, which controls the hydrogen bond interaction between schizophyllan molecular chains and their crystallization characteristics, thereby regulating the pore size, water absorption, drug release, mechanical properties and injectability of hydrogel materials. The obtained schizophyllan physical gel is an environmentally friendly material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the preparation of the physical gel of Schizophyllan in Example 1 of the present invention.
[0032] Figure 2 This is the sol-gel phase diagram of the physical gel of Schizophyllan in Example 1 of the present invention.
[0033] Figure 3 This is a Fourier transform infrared spectrum data diagram of the Schizophyllan physical gel of the present invention.
[0034] Figure 4 The differential scanning calorimetry data of the physical gel of Schizophyllan of the present invention are shown in Figure A, wherein Figure A shows the heat flow rate of the gel obtained by annealing at 120°C for different times, and Figure B shows the heat flow rate of the gel obtained by annealing at 135°C for different times.
[0035] Figure 5 The wide-angle X-ray scattering data of the physical gel of Schizophyllan of the present invention are shown in Figure A, wherein Figure A shows the strength of the gel obtained by annealing at 120°C for different times, and Figure B shows the strength of the gel obtained by annealing at 135°C for different times.
[0036] Figure 6 Schematic diagram of compression test of split-fold polysaccharide hydrogel annealed at different temperatures and the resulting stress-strain diagram, where Figure A is the stress-strain diagram of the gel annealed at 120°C for different times, and Figure B is the stress-strain diagram of the gel annealed at 135°C for different times.
[0037] Figure 7 Figure 3 is the dependence of the modulus of the schizophyllan hydrogel annealed at different temperatures on the annealing time.
[0038] Figure 8 The figure shows the dependence of the compression work of the schizophyllan hydrogel annealed at different temperatures on the annealing time.
[0039] Fig. 9 Rheological properties of schizophylla polysaccharide hydrogel.
[0040] Fig.10 The injectable properties of schizophylla polysaccharide hydrogel. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0042] The sources of the functional ingredients contained in the products involved in the following embodiments are as follows (only the functional ingredients are reflected, and the necessary auxiliary ingredients contained in other commercially available raw materials are not repeated):
[0043] Schizophyllan was purchased from Guangdong MaruMei Biotechnology Co., Ltd. under the trade name of Schizophyllan (SPG).
[0044] Example 1
[0045] This embodiment provides a method for preparing a schizophyllan hydrogel. The schematic diagram of the preparation method is shown in Figure 1 As shown, specifically:
[0046] (1) At room temperature, 700 g of a Schizophyllan dilute solution (0.32 wt / %) was weighed using an electronic balance, added to a round-bottom flask, and concentrated using a rotary evaporator to obtain 160 g of a Schizophyllan concentrated solution.
[0047] (2) The obtained Schizophyllan concentrated solution was poured into a 8 cm×8 cm PET plastic mold, heated at 55° C. for 24 h, and further concentrated to obtain Schizophyllan pregel (9.3 wt %).
[0048] (3) The obtained Schizophyllan pregel was immersed in DMF solvent for solvent exchange for 48 hours, and the DMF solvent was replaced every 3 hours to obtain SPG-DMF organogel.
[0049] (4) The SPG-DMF organogel was subjected to wet heat annealing treatment, and a series of SPG-DMF organogels with different properties were obtained by controlling different annealing temperatures (80-135°C) and insulation times (0-24h).
[0050] (5) The SPG-DMF organogel obtained in step (4) was exchanged with deionized water for 7 days, and the deionized water was replaced every 24 hours. The DMF in the gel was completely dialyzed to obtain the SPG hydrogel.
[0051] The results are as follows Figure 2 As shown, when the annealing temperature and time are higher than 100 °C and 3 h, respectively, the Schizophyllan solution can form a hydrogel.
[0052] Example 2
[0053] Structural and performance characterization of schizophyllan physical gel
[0054] (1) Fourier transform infrared spectroscopy (FT-IR) test: 2 mg of dried SPG sample and 200 mg of dried KBr powder were ground evenly in an agate mortar, pressed into thin slices by a tablet press, and then heated at 4000-500 cm -1 to scan.
[0055] The results are as follows Figure 3 As shown, 2800~3000cm -1 The peak is the C—H stretching vibration of sugars. The absorption peak in this area is the characteristic absorption peak of sugars. -1 The less sharp absorption peak is the C-H angular vibration. 1000~1200cm -1 The comparative absorption peaks are caused by two C—O stretching vibrations. 920cm-1, 850cm -1 The absorption peaks on the left and right are characteristic absorption peaks of β-type C-H vibration of pyranose. Furanose does not have such absorption peaks, so it can be known that the glycosidic bond of the two is β-type and the sugar ring is pyranose ring. -1 The broad peak is the stretching vibration of O—H. The absorption peak of the secondary O—H without hydrogen bond is generally at 3630cm -1 Nearby, the hydrogen bond within the molecule is at 3560cm -1 Nearby, the hydrogen bonds between molecules are at 3400cm -1 Below. 3395cm -1 The strong absorption peak of , indicating the existence of hydrogen bonds between molecules. With the increase of the insulation temperature, the absorption peak tends to move to a low frequency, which is due to the enhancement of hydrogen bonding, causing the absorption peak to red shift.
[0056] (2) Differential Scanning Calorimetry (DSC) Test: DSC 2500 (TA Instruments) was used to test the thermal characteristics of the polymer by performing a temperature scanning test between -30°C and 150°C at a heating rate of 10°C / min.
[0057] Use an electronic balance to weigh 3 mg of the dried samples of the split fold polysaccharide hydrogel obtained after annealing at 120℃ and 135℃ for different times, and put them into a crucible. The test uses a DSC2500 instrument. The test process is briefly described as follows: first, cool down from room temperature to -30℃ at a cooling rate of 10℃ / min, stay for 1min, and then increase the temperature from -30℃ to 150℃ at a heating rate of 10℃ / min to obtain the DSC curve of the test. The entire test process is carried out under nitrogen protection.
[0058] The results are as follows Figure 4 As shown in the figure, there is a huge endothermic peak between 30-100°C, which is caused by the change of the structure of SPG in this temperature range. In addition, as the insulation time increases, the endothermic peak gradually increases ( Figure 4 ).
[0059] (3) Wide-angle X-ray scattering (WAXS) test: The WAXS test instrument model is Rigaku HomeLab, using X-rays with a wavelength of The instrument is equipped with a Hypix-6000 photon direct-reading detector with an effective photosensitive area of 77.5 mm × 80.0 mm and a pixel size of 100 μm × 100 μm, which is used to acquire two-dimensional data of WAXS.
[0060] The specific test conditions are as follows: the exposure time is set to 50s, the distance from the sample to the detector is 69.17mm, and the samples are arranged in parallel and fixed on the sample holder, perpendicular to the X-ray direction. The one-dimensional scattering curve is obtained by processing the two-dimensional scattering data with Fit2D software. The dried samples of the schizophyllan hydrogel annealed at 120℃ and 135℃ were characterized respectively. The experimental results are shown in Figure 5 As shown, the diffraction peak at 2θ=5° represents a dense structure of triple helices.
[0061] (4) Compression test: Use a cutting machine with a standard cutting knife to cut the prepared hydrogel sample into samples with fixed test area specifications. Place the sample on the electronic universal testing machine Instron 5965, use a 10N force sensor, and continue to compress until the sample breaks, at which time the tensile machine stops collecting data. Finally, the compressive stress-strain curve of the hydrogel sample is derived. The whole process is completed at room temperature.
[0062] Take out the prepared split-fold polysaccharide hydrogel, cut out the sample with an 8mm circular cutter, and wipe the moisture on the surface of the hydrogel sample. In the compression test, the universal mechanical testing machine Instron 5965 was used for compression performance testing, using a 10N force sensor, and the compression rate of the upper fixture was 5mm / min until the sample was broken, and the tensile machine stopped collecting data, and finally the compressive stress-strain curve of the sample was obtained. The entire experimental process was completed at room temperature, and the compressive mechanical properties of the material depended on the annealing insulation temperature and insulation time.
[0063] The experimental results are as follows Figure 6 As shown. According to the compressive stress-strain curve, we obtained Young's modulus (E) and compression work (W). According to the relationship between Young's modulus, holding time and swelling ratio, we made Young's modulus-holding time curve, compression work-holding time curve and Young's modulus-swelling ratio curve, as shown Figure 7 , Figure 8 and Fig. 9 shown.
[0064] The study found that when the heat treatment time and temperature are higher, the hydrogel material has a lower swelling rate, a higher Young's modulus and compression work. At the same time, the swelling rate (Qv) of the gel and the Young's modulus (E) show a scaling relationship, indicating that the hydrogel formed by the schizophyllan solution is a neutral gel.
[0065] (5) Rheological analysis test: The rheological test was measured on the MCR 302e flat plate rotational rheometer of Anton Paar, Austria. The linear viscoelastic region of the material needs to be determined before the frequency sweep. First, the sample was strain scanned, the test frequency was 1 rad / s, the test temperature was 25°C, and the shear strain range was 0.01%-100%. According to the linear viscoelastic test results, the shear strain was fixed at 1%. Then a dynamic frequency sweep was performed with a fixed pressure of 0N.
[0066] Take out the prepared split-fold polysaccharide hydrogel, use an 8mm circular cutter to cut out the sample, and wipe the moisture on the surface of the hydrogel sample. Use the MCR 302e flat plate rotational rheometer of AntonPaar, Austria, to test the storage modulus G′ and loss modulus G″ of the gel sample at room temperature in sweep mode, and use a stainless steel parallel plate with a diameter of 8mm as the test fixture. The above tests all record data such as storage modulus (G′), loss modulus (G″). Different annealing times can significantly change the mechanical properties of the hydrogel sample. The experiment is as follows Fig. 9 As shown in the figure, the dynamic modulus increases with the frequency, and G′ is always greater than G″ in the entire scanning frequency range. At the same frequency, with the increase of annealing time, the G′ of the sample increases.
[0067] At the same time, rheological tests of all hydrogel samples showed that their modulus had no dependence on the loading frequency, proving that the hydrogel formed by the schizophyllan solution was an elastic gel.
[0068] (6) Injectability
[0069] Because the triple helix structure of the gel can be destroyed under the action of high shear, the prepared gel material has injectable properties. For example, we put the prepared hydrogel sample into a syringe, and during the extrusion process, the gel can be extruded to form a pattern ( Fig.10 ).
[0070] Summary: Through the analysis of the test results of the above examples, it can be seen that the mechanical properties of the hydrogel are closely related to the annealing insulation temperature and insulation time. Changing the annealing insulation temperature or insulation time can significantly regulate the mechanical properties of the split-fold polysaccharide hydrogel (modulus: 12-1049Pa, compression work: 4-286, swelling degree: 2-20). The split-fold polysaccharide hydrogel prepared by the present invention has an excellent injection molding effect and is expected to be used in the field of cosmetic plastic surgery.
[0071] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the preparation method of the injectable hydrogel based on Schizophyllan and its products and applications, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0072] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0073] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A method for preparing an injectable hydrogel based on Schizophyllan, characterized in that: The preparation method comprises: (1) concentrating the aqueous solution containing Schizophyllan to obtain a Schizophyllan pregel; (2) soaking the schizophyllan pregel in an organic solvent to obtain an organogel; (3) subjecting the organogel to wet annealing treatment; (4) soaking the gel obtained in step (3) in deionized water and freeze-drying to obtain; The mass percentage of Schizophyllan in the Schizophyllan pregel in step (1) is 5-60%; The organic solvent in step (2) comprises any one of dimethylacetamide, dimethyl sulfoxide, formamide, and acetonitrile, or a combination of at least two thereof; The wet annealing temperature is 100-150° C. and the time is 3-72 h.
2. The method for preparing an injectable hydrogel based on Schizophyllan according to claim 1, characterized in that: The concentration temperature in step (1) is 60-90°C and the time is 2-5 hours.
3. The method for preparing an injectable hydrogel based on Schizophyllan according to claim 1, characterized in that: The immersion time in the organic solvent is 6-72 h.
4. The method for preparing an injectable hydrogel based on Schizophyllan according to claim 1, characterized in that: In step (2), the organic solvent is replaced every 2-3 h.
5. The method for preparing an injectable hydrogel based on Schizophyllan according to claim 1, characterized in that: The soaking time in step (4) is 7-10 days.
6. The method for preparing an injectable hydrogel based on Schizophyllan according to claim 1, characterized in that: In step (4), the deionized water is replaced every 20-28 h.
7. A hydrogel prepared by the method for preparing an injectable hydrogel based on Schizophyllan according to any one of claims 1 to 6.
8. Use of the hydrogel according to claim 7 in cosmetics.
Citation Information
Cited By
Injectable schizophyllan gel drug delivery system and preparation method thereof
CN120884531A
Injectable schizophyllan gel drug delivery system and method of preparation thereof
CN120884531B